COVID-19 Vaccination Behavior Among Frontline Healthcare Workers in Pakistan: The Theory of Planned Behavior, Perceived Susceptibility, and Anticipated Regret - Khayyam, Muhammad; Chuanmin, Shuai; Salim, Muhammad Asad; Nizami, Arjumand; Ali, Jawad; Ali, Hussain; Khan, Nawab; Ihtisham, Muhammad; Anjum, Raheel (Frontiers in Psychology, 2022)
Healthcare workers in Pakistan are still fighting at the frontline to control the spread of SARS-CoV-2 and have been identified as the earliest beneficiaries for COVID-19 vaccination by the health authorities of the country Besides, the high vaccination rates of frontline healthcare workers (FHWs) is essential to overcome the ongoing pandemic and reduce the vaccines hesitancy among the general population. The current research employed the theory of planned behavior (TPB) to investigate the COVID-19 vaccination behavior among FHWs in Pakistan as well as the predictors of such behavior. Following the epidemic control and prevention policies, a representative sample of 680 FHWs were accessed to fill in the questionnaire evaluating the components of the TPB. Moreover, the potential role of anticipated regret and perceived susceptibility on COVID-19 vaccination behavior was also assessed. The PLS-SEM results revealed that the TPB components, as well as the anticipated regret, have positive associations with the COVID-19 vaccination behavior. The results further confirmed that perceived susceptibility positively affects the anticipated regret, attitude, and subjective norm to vaccinate against SARS-CoV-2. The perceived susceptibility also has a positive association with COVID-19 vaccination behavior through the mediation of anticipated regret, attitude, and subjective norm. Our findings highlighted the importance of COVID-19 vaccination among healthcare workers, which can be applied to reduce vaccine hesitancy among the general public.